The Consciousness of a Partisan: Rather Die than Be a Slave - Mickūnas, Algis (Tautosakos darbai, 2017)
The topic addresses the very “essence” of what comprises a human being. While there are many answers employing various categorical and even cultural definitions, our quest is philosophical, leading to a distinction of a “species” called “homo sapiens” into “natural slaves” and “free beings”. The distinction is based not on species similarities, but on activity. Societies, living under the premise of pure power relationships – autocratic, theocratic, dictatorial – where causal explanations of action are prevalent, cannot invoke such notions as freedom, responsibility, rights, truthfulness, honor, dignity, since such designations have no meaning in such societies. One such society, the Soviet empire, invaded and destroyed Lithuanian Political Society. The latter is premised on open public space in which all issues are discussed rationally, with every citizen having a right, duty and responsibility to maintain the free arena of public dialogue and thus the citizens’ upholding of his / her autonomy, equality, responsibility and honor. This means that political society, founded by classical Greeks is one where human beings can exercise what slaves cannot: their human essence, in contrast to the sub-human societies living only in power relationships. The slave Soviet empire was joined by many Lithuanians who also became servants and slaves of that empire. Others chose to forfeit all their possessions and even lives – the partisans – in order to remain free, responsible, and thus human. Their self-understanding: it is better to die on one’s feet than to live on one’s knees.
Keywords: -